2009
DOI: 10.1103/physreve.79.055203
|View full text |Cite
|
Sign up to set email alerts
|

Globally clustered chimera states in delay-coupled populations

Abstract: We have identified the existence of globally clustered chimera states in delay-coupled oscillator populations and find that these states can breathe periodically and aperiodically and become unstable depending upon the value of coupling delay. We also find that the coupling delay induces frequency suppression in the desynchronized group. We provide numerical evidence and theoretical explanations for the above results and discuss possible applications of the observed phenomena.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 30 publications
0
54
0
Order By: Relevance
“…(1) and discovered a motivating phenomenon of the existence of GCC states (note that system (1) consists of two populations of identical oscillators) as shown in Fig. 1, and reported briefly in [13]. Interestingly enough we found that the coupling delay induces such phenomena where the system of identical delay-coupled populations splits into desynchronized and synchronized groups.…”
Section: Numerical Studiesmentioning
confidence: 67%
See 2 more Smart Citations
“…(1) and discovered a motivating phenomenon of the existence of GCC states (note that system (1) consists of two populations of identical oscillators) as shown in Fig. 1, and reported briefly in [13]. Interestingly enough we found that the coupling delay induces such phenomena where the system of identical delay-coupled populations splits into desynchronized and synchronized groups.…”
Section: Numerical Studiesmentioning
confidence: 67%
“…These boundaries are the same as those for the in-phase and anti-phase synchronization states obtained from Eq. (13). Dot-dashed and dashed curves correspond to in-phase and anti-phase synchronization states of (16).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One proven modification is the inclusion of non-local effects of the geometry of the system that has been shown to lead to a co-existence of partially synchronized and partially asynchronized states of oscillators as a steady-state solution. Such states, addressed as chimera states, are the subject of recent theoretical and experimental studies (Kuramoto and Battogtokh, 2002;Abrams and Strogatz, 2004;Abrams et al, 2008;Ko and Ermentrout, 2008;Omel'chenko et al, 2008;Sethia et al, 2008;Sheeba et al, 2009;Laing, 2009a, b;Laing et al, 2012;Martens et al, 2013;Yao et al, 2013;Rothkegel and Lehnertz, 2014;Kapitaniak et al, 2014;Pazó and Montbrió, 2014;Panaggio and Abrams, 2014;Zhu et al, 2014;Gupta et al, 2014;Vasudevan and Cavers, 2014a, b). We focus our present study on defining a Kuramoto model with a phase lag that would accommodate the existence of chimera states.…”
Section: Mathematical Model Of the Earthquake Sequencingmentioning
confidence: 99%
“…It was shown that in a globally coupled network of oscillators with delay feedback, the single spatially connected region was replaced by a number of spatially disconnected regions of coherence with regions of incoherence in between. These states were named clustered chimera states [9,10]. Chimera states have been described as the natural link between coherent and incoherent states [11].…”
Section: Introductionmentioning
confidence: 99%